L’Histoire en représentation dans le dessin de presse britannique d’après 1945 - Gilbert Millat (Revue Française de Civilisation Britannique)
This article deals with British political cartoons published between the second half of the 20th and the early 21st centuries. There is a case for arguing that this media belongs to the field of cultural history, especially if we try to consider the tendency for cartoonists to give their personal interpretation of contemporary historical events. Consequently, a number of cartoons by Michael Cummings, Nicholas Garland and Steve Bell are analyzed in order to pinpoint the plasticity of this hybrid of picture and text, but also its huge potential for tirelessly revisiting Britain’s visual heritage. Indeed, in order to comment topical events, cartoons appeal to newspaper readers’ memory whether by reinterpreting the Second World War or other defining moments in British history.